Engaging visitors in cultural and recreational experience at museums - Loureiro, S. M. C.; Ferreira, E.S. (Anatolia, 2018)
The aim of this study is to establish the relationships between (i) motivational drivers (serious leisure, meaningfulness, prior knowledge) and levels of engagement; (ii) and between levels of engagement and outcomes (word-of-mouth and passionate desire to return). The proposed model is tested with a sample of 461 visitors’ experiences at Museum of Coaches in Lisbon, Portugal. Serious leisure and prior knowledge are important motivators of engagement with museums. Engaged visitors are more willing to return and spread the word to others. The findings contribute to better understand the visitors’ perceptions of museums as tourist attractions. Several implications can be pointed out from the study and interesting directions for future research.